Decision making tool for industrialised building system adoption through integrated life cycle cost analysis - Siti Mazzuana Shamsuddin, 1980-, author; Rozana Zakaria, supervisor; Nur Izieadiana Abidin, supervisor; Fakulti Kejuruteraan. Sekolah Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2020)
Thesis (Ph.D (Kejuruteraan Awam)) - Universiti Teknologi Malaysia, 2020